The Liquidity Risk of REITs. Issue 1 (15th February 2021) - DiBartolomeo, Jeffrey A.; Gatchev, Vladimir A.; Harrison, David M.
Abstract: This study examines the liquidity risk of real estate investment trusts (REITs) as measured by their return sensitivity to marketwide liquidity shocks. Due to their unique dividend payout rules and associated high cash payouts, REITs should benefit investors by reducing their reliance on the stock market to satisfy liquidity needs. Using a sample of 440 equity REITs from 1980 through 2015, we find empirical evidence consistent with this paradigm along four key dimensions. First, unlike non-REIT real estate firms, REITs exhibit a negative sensitivity to marketwide liquidity shocks. More specifically, when marketwide liquidity declines, REIT prices tend to increase relative to the broader stock market. Second, our findings are not property type specific, but rather are evident across broad classifications of property type sectors. Third, consistent with the importance of cash flow stability, smaller REITs provide protection against liquidity risk only when their dividend frequency is relatively high. Finally, examining only those firms changing their REIT status within the sample period, we find marketwide liquidity risk is lower when these firms operate as REITs than when they operate as non-REITs. Taken together, these findings provide support for the notion that investors view dividend payouts as a source of enhanced liquidity, and further, that REITs, as a security class with relatively high regulatory mandated payout requirements, provide investors with an important benefit in the form of reduced liquidity risk.